Hjalmar Torp. La rotonde palatine à Thessalonique: Architecture et mosaïques. 2 Vols. pp. 568, 192 col. and b/w ills and plates. 2018. Athens: Éditions Kapon. ISBN: 978-618-5209-37-7, hardcover €86. - Elsner, Jaś (Journal of Greek Archaeology, 2020)
The great American satirist, Tom Lehrer, once said (in relative youth) ‘when Mozart was my age, he’d been dead two years’. When Hjalmar Torp began to write about the Rotunda (or Church of St George) in Thessaloniki, this reviewer hadn’t been born for 8 years… Torp’s first contribution to the study of this remarkable and enigmatic building was published in 1954. It was the beginning of a string of discussions. If anyone knows this monument really well, it is the great – now 95-year-old – doyen of Norwegian early Christian archaeology. What he has published here is a beautifully produced and lovingly written summa of a lifetime’s work, with publications spanning French, Norwegian and English over 65 years – a period that included significant events in the lifetime of the building itself, such as the damage of the earthquake of 1978 and the painstaking restorations thereafter. The book is commanding, comprehensive and fundamental, and the addition of a brief typology of the portraits of the saints by the distinguished art historian Bente Kiilerich is welcome (pp. 187-93).